The Crisis of Religious Identity in the Young Generation - Anggreni Bako; Azwar Ananda (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2023)
This research aims to determine the impact of identity crisis on adolescents due to online games in Simberuna Village, Sitellu Tali Urang Jehe District, Pakpak Bharat Regency. This research is a qualitative descriptive type of research that describes and explains in the form of an in-depth description and analysis of a real situation and situation, namely regarding